Micro analysis to map the glycome code. Issue 9 (25th March 2014) - Simone, Giuseppina
<x xml:space="preserve">Abstract</x> Proteins play pivotal functions in cells; the study of these proteins and functions is the realm of proteomics. Less appreciated is that the proteins can be sugar coated and that glycosylation affects how the immune system recognizes the protein, as being friend or foe. Protein glycosylation and glycan‐protein interactions are involved in malignant processes, including those that underlie tumor, diabetes, and Alzheimer's disease. Some aspects of the glycome, including the role that simple glycans and their derivates have in the modulation of cellular behavior, have not yet been elucidated. Novel interdisciplinary technologies are needed to improve our understanding of those fields. Here, we describe the hierarchical levels of glycan structure and discuss the potential of microfluidics to gain an improved understanding of those mechanisms.